PEMIKIRAN IBN QAYYIM AL-JAUZIYAH TENTANG HILAH DAN IMPLIKASINYA DALAM FIKIH - Elfia, Elfia (JURIS (Jurnal Ilmiah Syariah), 2015)
In discussing about the issue of hilah, Ibnu Qayyim al-Jauziyyah has his own understanding toward the issue which seemed to be different from the concept which was very popular among fuqahas. To the  best of his understanding, hilah is basically a form of action (deed) which seem to fool the law of Allah. Fooling the laws of Allah endangers Islam since it only fulfills those who promoted hilah and, therefore, withdraw the willingness to enforce Islamic laws (syara). Ibnu Qayyim emphasized that hilah in Islam is only intended to promote legalization of the forbiddens (haram) and in turn, will jeopardize the compulsory ones by presenting reasons. Those are forbidden (haram) viewed from various perspectives. The permission for hilah violates sadd al-zari’ah since the only islamic law maker, Allah has shut all possible attempts that may lead to destruction. Hilah is a form of manipulation toward Allah and any manipulative attempts toward Allah are forbidden (haram). There are many examples of hilah illustrated by Ibn Qayyim in his book kitab i’lam al-Muwaqi’in. Though Ibn Qayyim views hilah is forbidden (haram) in general, including those are approved by Abu Hanifah, however, some are still tolerated for particular conditions.Kata kunci: hilah, sadd al-dzari‘ah, fikih